Antiandrogens for the treatment of COVID‐19 patients: A meta‐analysis of randomized controlled trials. Issue 4 (18th April 2023) - Cheema, Huzaifa Ahmad; Rehman, Aqeeb Ur; Elrashedy, Asmaa Ahmed; Mohsin, Aleenah; Shahid, Abia; Ehsan, Muhammad; Ayyan, Muhammad; Ismail, Heba; Almas, Talal
Abstract: Antiandrogens may carry a potential benefit as a therapeutic agent against COVID‐19. However, studies have been yielding mixed results, thus hindering any objective recommendations. This necessitates a quantitative synthesis of data to quantify the benefits of antiandrogens. We systematically searched PubMed/MEDLINE, Cochrane Library, clinical trial registers, and reference lists of included studies to identify relevant randomized controlled trials (RCTs). Results from the trials were pooled using a random‐effects model and outcomes were reported as risk ratios (RR) and mean differences (MDs) with 95% confidence intervals (CIs). Fourteen RCTs with a total sample size of 2593 patients were included. Antiandrogens yielded a significant mortality benefit (RR 0.37; 95% CI; 0.25–0.55). However, on subgroup analysis, only proxalutamide/enzalutamide and sabizabulin were found to significantly reduce mortality (RR 0.22, 95% CI: 0.16–0.30 and RR 0.42, 95% CI: 0.26–0.68, respectively), while aldosterone receptor antagonists and antigonadotropins did not show any benefit. No significant between‐group difference was found in the early or late initiation of therapy. Antiandrogens also reduced hospitalizations and the duration of hospital stay, and improved recovery rates. Proxalutamide and sabizabulin may be effective against COVID‐19, however, further large‐scale trials are needed to confirm these findings.